Airline revenue management performance measurement of South African Airways origin-destination revenue management - Githiri, Duncan Wanjau (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
Revenue Management (RM) in the airline industry is the practise of selling fixed capacity as a service over a finite time horizon. The market is characterised by the customers' willingness to pay different prices for the service. This creates the opportunity to target different customer segments and use price differential to attain the optimal passenger fare mix to maximise revenue. The aim is to maximise revenue and an airline can expect revenue increase of between 3 to 7 percent with the successful implementation of a Revenue Management system. The question of whether the revenue increase can be attributed to the RMS is crucial in determining its level of success and validating the optimisation strategy applied (Rannou and Melli, 2003). South African Airways (SAA) migration from Leg-based optimisation to Origin-Destination (O&D) network based revenue management optimisation created the opportunity for this study to measure and evaluate the RMS performance. Revenue performance measuring tools using inventory systems data to measure RMS performance, ASK (Available Seat Kilometre), RASK (Revenue per Available Seat Kilometre), CASK (Cost per Available Seat Kilometre), RPK (Revenue Passenger Kilometre) and cabin factor yield. The limitations relating to the performance measuring tools utilising inventory system data, is the inability for continuous measurement and the isolation of the impact to revenue due to the RMS on its own. In seeking to gauge the performance of the O&D optimisation, the Revenue Opportunity Model (ROM) is applied. ROM is a post departure measuring tool utilised to continuously measure and isolate the contribution of the RMS on SAA's O&D network. The revenue opportunity achieved versus the potential revenue was assessed. A revenue comparison of the airlines 2014 and 2015 financial year is performed. The results of the analysis showed the O&D optimisation yielded positive revenue capture on routes that applied the correct optimisation strategy. Recommendations on the optimisation strategy to be applied on routes having average or low revenues captured are presented. The aim is to provide the SAA revenue management department with tangible solutions that would result in increased revenue for the SAA network.
Keywords: Revenue management; Airlines -- Finance; Performance -- Measurement; Airlines -- Rates -- Mathematical models; South African Airways